2023
DOI: 10.1152/ajprenal.00193.2023
|View full text |Cite
|
Sign up to set email alerts
|

Dietary anions control potassium excretion: it is more than a poorly absorbable anion effect

Abstract: Background: The urinary potassium excretion machinery is upregulated with increasing dietary potassium, but the role of accompanying dietary anions remains inadequately characterized. Poorly absorbable anions, including HCO3-, are thought to increase K+ secretion through a transepithelial voltage effect. Here we test if they also influence the potassium secretion machinery. Methods: Wild-type mice, aldosterone synthase knockout (AS-KO), or pendrin knockout mice were randomized to control, high KCl, or high KHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Although, as just discussed, the K þ loss is often associated with K þ channel activity like ROMK in principal cells, a recent study demonstrated that pendrin was required for K þ excretion under a high KHCO 3 diet [46]. In our recent study, we hypothesized that pendrin and KCC3a are functionally coupled (Fig.…”
Section: Function Of K-cl Cotransporters-3 In the Kidneymentioning
confidence: 79%
“…Although, as just discussed, the K þ loss is often associated with K þ channel activity like ROMK in principal cells, a recent study demonstrated that pendrin was required for K þ excretion under a high KHCO 3 diet [46]. In our recent study, we hypothesized that pendrin and KCC3a are functionally coupled (Fig.…”
Section: Function Of K-cl Cotransporters-3 In the Kidneymentioning
confidence: 79%
“…There is also recent evidence that alkalosis can stimulate KHCO 3 secretion by intercalated cells, through the combined action of pendrin and the KCl cotransporter KCC3a. 9…”
mentioning
confidence: 99%
“…There is also recent evidence that alkalosis can stimulate KHCO 3 secretion by intercalated cells, through the combined action of pendrin and the KCl cotransporter KCC3a. 9 In hypokalemia, the goal of K 1 supplementation is clear: to raise plasma [K 1 ]. In a cardiovascular context, it is not known whether the increased cellular uptake and excretion by the kidneys with K citrate supplements are desirable.…”
mentioning
confidence: 99%